The transparent leader : a business fable of clear and effective leadership communication - Gladis, Stephen D. (HRD Press, 2009)
Written as a business leadership fable, The Transparent Leader is the story of a smart emerging leader, Stephanie Marcus, as she navigates the challenging world of business. Fortunately, Steph meets Lou Donaldson, a public relations CEO near the end of his career, at a local gym where she works out daily. Lou acts as a friend, informal coach, and mentor as he guides Steph through the complicated business ecosystem in which she finds herself. Throughout the story, Steph learns about clear leadership communication as she also adapts and changes and becomes a more transparent-clear and open-leader. At the same time, she learns Lou's personal story, which helps her fully appreciate his wisdom.